Importância da região anteroventral do terceiro ventrículo (AV3V) no controle cardiovascular e do equilíbrio hidroeletrolítico - Vieira, Alexandre A. [UNESP]; De Paula, Patricia M. [UNESP]; De Luca Jr., Laurival A. [UNESP]; Colombari, Débora S. A. [UNESP]; Colombari, Eduardo [UNESP]; Menani, José Vanderlei [UNESP] (My University, 2006)
The maintenance of the arterial pressure in normal levels is important for the homeostasis of body fluids. The central nervous system regulating sympathetic and parasympathetic autonomic efferent can adjust arterial pressure which allows animals or human to face different daily activities with the best performance. Different central areas are responsible for the control of autonomic discharges to cardiovascular system and many of them are also involved in the control of fluid electrolyte balance. One of these areas is the tissue surrounding the anteroventral third ventricle (AV3V region) localized in the forebrain and a main central site for angiotensin II receptors and osmoreceptors. The AV3V lesions impair the development of many models of experimental hypertension in rats and the pressor responses to different stimuli. Lesions of the AV3V region also reduce dipsogenic responses to angiotensin II, central cholinergic activation, water deprivation and increase in plasma osmolarity, atrial natriuretic peptide secretion produced by body fluid expansion and the increase in renal excretion to central cholinergic activation. Recent evidence also suggests the participation of AV3V region in pressor responses produced by the activation of medullary mechanisms.
Importance of the anteroventral third ventricle (AV3V) region in cardiovascular control and hydromineral balance
Keywords: Angiotensin; Glutamate; Hypertension; Hypothalamus; Sympathetic Nervous System; angiotensin; angiotensin 2 receptor; arterial pressure; autonomic nervous system; brain third ventricle; cardiovascular function; cardiovascular system; central nervous system; cholinergic activity; conference paper; electrolyte balance; experimental model; forebrain; homeostasis; hypertension; hypothalamus; nonhuman; osmoreceptor; plasma osmolarity; pressor response